Ovarian Mass Causing Paradoxical MI and Leg Ischaemia - K. J. Griffin; M. A. Bailey; J. P. Greenwood; L. Barker; T. Nicholson; D. J. A. Scott (Case Reports in Vascular Medicine)
Paradoxical embolus through a patent foramen ovale is a well-reported phenomenon. Clinical consequences include stroke, intestinal infarction, lower limb ischaemia, and even acute myocardial infarction (MI), via embolisation to the coronary arteries. We present a case of acute MI, cardiogenic shock, and cardiac arrest caused not by this mechanism, but by embolisation of thrombotic material to the aortic root with transient complete occlusion of the left main stem (LMS) coronary artery. During percutaneous coronary intervention to treat this occlusion the thrombus became lodged at the aortic bifurcation causing lower limb ischaemia. Despite successful treatment of this via bilateral groin exploration and thromboembolectomy the patient became increasingly acidotic and an abdominal and pelvic CT scan was performed. This revealed the source of the thrombus to be the patient’s congested and compressed pelvic veins which were the result of a large, previously undiagnosed ovarian malignancy with metastatic spread. Although very unusual we feel this case highlights an important differential in the diagnosis of anterolateral MI and images similar to those presented here are previously unreported in the literature.